1999
DOI: 10.1002/(sici)1099-1026(199909/10)14:5<322::aid-ffj837>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of structure and molecular properties of terpenoids in determining their antimicrobial activity

Abstract: The minimum inhibitory concentrations (MIC) of 60 terpenoids against Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus and Candida albicans have been determined. Hierarchical cluster analysis was used to group the compounds into five groups according to their activity patterns against the four microorganisms. K‐Means cluster analysis was then used to confirm these groupings and to show the differences in the activity patterns of the groups. Ten molecular properties of the terpenoids, either calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
289
3
23

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 435 publications
(353 citation statements)
references
References 33 publications
21
289
3
23
Order By: Relevance
“…D'une façon générale, les activités antibactériennes et antifongiques de l'huile de géranium Bourbon peuvent être attribuées principalement aux alcools terpéniques (citronellol, géraniol, linalol) qui représentent environ 50,07% des constituants de cette huile. En effet, les terpènes oxygénés sont des agents antimicrobiens très actifs (Gueldener et al, 1985 ;Faid et al, 1996 ;Griffin et al, 1999 ;Dorman & Deans, 2000 ;Kamran et al, 2001 ;Satrani et al, 2006). En outre, plusieurs études ont montré qu'en raison de la complexité chimique des huiles essentielles une activité antimicrobienne beaucoup plus prononcée que celle prévisible pour les composés majoritaires peut être due à la présence d'interactions synergiques entre composés (Franchomme, 1981 ;Kurita & Koik, 1982 ;Gueldener et al, 1985 ;Inouy et al, 2000 ;Burt, 2004 ;vinda-Martos et al, 2008).…”
Section: Sensibilité Des Microorganismes Aux Huiles Essentiellesunclassified
“…D'une façon générale, les activités antibactériennes et antifongiques de l'huile de géranium Bourbon peuvent être attribuées principalement aux alcools terpéniques (citronellol, géraniol, linalol) qui représentent environ 50,07% des constituants de cette huile. En effet, les terpènes oxygénés sont des agents antimicrobiens très actifs (Gueldener et al, 1985 ;Faid et al, 1996 ;Griffin et al, 1999 ;Dorman & Deans, 2000 ;Kamran et al, 2001 ;Satrani et al, 2006). En outre, plusieurs études ont montré qu'en raison de la complexité chimique des huiles essentielles une activité antimicrobienne beaucoup plus prononcée que celle prévisible pour les composés majoritaires peut être due à la présence d'interactions synergiques entre composés (Franchomme, 1981 ;Kurita & Koik, 1982 ;Gueldener et al, 1985 ;Inouy et al, 2000 ;Burt, 2004 ;vinda-Martos et al, 2008).…”
Section: Sensibilité Des Microorganismes Aux Huiles Essentiellesunclassified
“…activity, but it is an essential characteristic to a biotransforming agent. Generally, the minimum inhibitory concentration (MIC) of limonene against some bacteria and yeasts are lower than 2% (14), although some fungi, e.g. Penicillium digitatum, presents only a small reduction on its bioconversion activity in concentrations of 4-8% limonene (27) and some bacteria, e.g.…”
Section: Limonene Resistant Microorganismsmentioning
confidence: 99%
“…In the presence of carvacrol and thymol (2 MIC), the mean biofilm formation values were equal to 91±0.8 and 86±2.1% for P. aeruginosa (ATCC 27853), and 62±1.2% and 54±5.9% for P. aeruginosa (CIP A22), and 90±2.5% and 70±4.3 for P. aeruginosa (IL5), respectively. Carvacrol and thymol have a log Po/w of 3.64 and 3.30, respectively (Griffin et al, 1999;Ultee et al, 2002). Weber and de Bont (1996) reported that compounds with a log Po/w value higher than 3 are highly potent on disturbing cell membrane.…”
Section: Resultsmentioning
confidence: 99%